Towards broad-spectrum protection: the development and challenges of combined respiratory virus vaccines - Wang, Yang; Wei, Xiaotong; Liu, Yang; Li, Shengfeng; Pan, Weiqi; Dai, Jun; Yang, Zifeng (Frontiers in Cellular and Infection Microbiology, 2024)
In the post-COVID-19 era, the co-circulation of respiratory viruses, including influenza, SARS-CoV-2, and respiratory syncytial virus (RSV), continues to have significant health impacts and presents ongoing public health challenges. Vaccination remains the most effective measure for preventing viral infections. To address the concurrent circulation of these respiratory viruses, extensive efforts have been dedicated to the development of combined vaccines. These vaccines utilize a range of platforms, including mRNA-based vaccines, viral vector vaccines, and subunit vaccines, providing opportunities in addressing multiple pathogens at once. This review delves into the major advancements in the field of combined vaccine research, underscoring the strategic use of various platforms to tackle the simultaneous circulation of respiratory viruses effectively.